Pengembangan Model Regulasi untuk Pewarisan Digital Aset Kripto: Perspektif Hukum Indonesia: Developing a Regulatory Model for Digital Inheritance of Cryptocurrency Assets: the Indonesian Legal Perspective - Raharningtyas Marditia, Putri Purbasari; Nazhif Kuncoro , Rafi Radithya (Perspektif Hukum, 2025)
The rapid development of digital technology has introduced new forms of wealth, with cryptocurrencies being a prominent example. In Indonesia, these assets have gained significant popularity as investment instruments, but their intangible nature and reliance on private keys for ownership pose serious legal challenges in the realm of inheritance. The research aims to analyze the legal position of cryptocurrencies as inheritable objects and to formulate a viable inheritance mechanism that ensures legal certainty for heirs. This research uses normative legal methods by analyzing relevant statutory law, legal doctrine, and comparative perspectives of the legal system in the Netherlands and the United States. The findings show that cryptocurrencies meet the criteria to be classified as movable and intangible objects, in accordance with Articles 503 and 504 of the Civil Code. Nevertheless, a significant gap was identified between the legal rights of heirs (de jure) and their practical ability to access assets (de facto), due to the lack of uniform technical regulations. Therefore, the research concludes that two strategic steps are needed: the issuance of national technical guidelines to standardize inheritance claims procedures and the development of a "Digital Executor" mechanism, which is officially empowered to manage the digital assets of the deceased.